Peran dan Kontribusi Syaikh Nawawi Al-Bantani dalam Kajian Hadis di Indonesia - Raffi’u, Aliyya Shauma; Kudus, Abdul; Jaenudin, Dindin; Hafidz, Ai Raffi’ah (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Shaykh Nawawi al-Bantani is one of the scholars who has made significant contributions to various fields of Islamic knowledge in Indonesia, including the hadiths of the Prophet. Therefore, this research aims to describe the role and contribution of Shaykh Nawawi al-Bantani in the field of hadith. The method used in this research is descriptive with a literature review approach. The analytical technique employed is qualitative content analysis. The results of this research include: Shaykh Nawawi al-Bantani's role and contribution to the study of hadith in the Indonesian archipelago cannot be separated from the roles of his disciples (santri) and his works, which continue to be taught to the community, especially within the environment of Islamic boarding schools (pesantren).